Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) x3 = x2
13=12
\(\Rightarrow\)x=1
b) 56: 5x = 54
5x=56:54
5x=52
x=2
c)52x-3-2.52=52.3
52x-3-50=75
52x-3=75+50
52x-3=125
52x-3=53
2x-3=3
2x=3+3
2x=6
x=6:2
x=3
a) 25 . 5x+2 = 625
=> 5x+2 = 625 : 25
=> 5x+2 = 25
=> 5x+2 = 52
=> x + 2 = 2
=> x = 0
b) 9x-5 . 9x = 729
=> 9x-5+x = 93
=> x-5+x = 3
=> 2x - 5 = 3
=> 2x = 8
=> x = 4
c) (3x - 2)4 = 0
=> (3x - 2)4 = 04
=> 3x - 2 = 0
=> 3x = 2
=> x = \(\frac{2}{3}\)
d) 2x+6 . 2 = 128
=> 2x+6 = 64
=> 2x+6 = 26
=> x + 6 = 6
=> x = 0
a)(x-2)5=243
\(\Leftrightarrow\left(x-2\right)^5=3^5\)
\(\Rightarrow x^5=3^5+2^5=5^5\)
\(\Rightarrow x=5\)
Bài 1:
a)12,5 x (-5/7) + 1,5 x (-5/7)
=-5/7*(12,5+1,5)
=-5/7*14
=-10
b)(-1/4) x (6|2/11) + 3|9/11 x (-1/4)
=-1/4*(68/11+42/11)
=-1/4*10
=-5/2
c tương tự
d)\(\frac{9^8\cdot4^3}{27^4\cdot6^5}=\frac{\left(3^2\right)^8\cdot\left(2^2\right)^3}{\left(3^3\right)^4\cdot\left(2\cdot3\right)^5}=\frac{3^{16}\cdot2^6}{3^{12}\cdot2^5\cdot3^5}=\frac{3^{16}\cdot2^5\cdot2}{3^{16}\cdot3^1\cdot2^5}=\frac{2}{3}\)
Bài 2:
a)Ta có:
2800=(28)100=256100
8200=(82)100=64100
Vì 256100>64100 =>2800>8200
b)Ta có:
1245=(123)15=172815
Vì 62515<172815 =>62515<1245
a) |x-1|-2x=5
\(\Leftrightarrow\) x - 1 - 2x = 5 (đk: x\(\ge\)1 ) (1)
hoặc -x + 1 - 2x = 5 ( đk: x < 1) (2)
(1): \(\Leftrightarrow\) x - 2x = 5 + 1
\(\Leftrightarrow\) - x = 6
\(\Leftrightarrow\) x = -6 (ko thỏa mãn)
(2): \(\Leftrightarrow\) -x + 1 - 2x = 5
\(\Leftrightarrow\) -3x = 4
\(\Leftrightarrow\) x = \(\frac{-4}{3}\) (thỏa mãn)
Vậy: x = \(\frac{-4}{3}\)
b) |9-7x|=5x-3
\(\Leftrightarrow\) 9 - 7x = 5x - 3 (đk: \(\le\) \(\frac{9}{7}\) ) (1)
hoặc -9 + 7x = 5x - 3 (đk: x > \(\frac{9}{7}\) ) (2)
(1): \(\Leftrightarrow\) -7x-5x = -3-9 \(\Leftrightarrow\) -12x = -12 \(\Leftrightarrow\) x = 1 ( thỏa mãn)
(2): \(\Leftrightarrow\) 7x - 5x = -3 + 9 \(\Leftrightarrow\) 2x = 6 \(\Leftrightarrow\) x = 3 ( thỏa mãn)
Vậy: x= 1; 3
c) 5x+2 = 625
\(\Leftrightarrow\) 5x . 52 = 54
\(\Leftrightarrow\) 5x = \(\frac{5^4}{5^2}\)= 52
\(\Leftrightarrow\) x = 2
d) (2x - 3)2 = 36
\(\Leftrightarrow\) \(\left[{}\begin{matrix}2x-3=6\left(đk:x\ge\frac{3}{2}\right)\text{}\Leftrightarrow x=4,5\left(TMĐK\right)\\2x-3=-6\left(đk:x< \frac{3}{2}\right)\Leftrightarrow x=-1,5\left(TMĐK\right)\end{matrix}\right.\)
Vậy: x = 4,5; -1,5
a,12,5x(-5/7)+1,5x(-5/7)
=-125/14+-15/14
=-10
2,2mu800>8 mu 200
6254 lon hon 12
a) \(5^x.5=625\)
\(\Rightarrow5^x=125=5^3\)
\(\Rightarrow x=3\)
b) \(3^x=9.27\)
\(\Rightarrow3^x=3^2.3^3=3^5\)
\(\Rightarrow x=5\)
c) \(\left(x-6\right)^2=9\) .
\(\Rightarrow\orbr{\begin{cases}x-6=-3\\x-6=3\end{cases}}\Rightarrow\orbr{\begin{cases}x=3\\x=9\end{cases}}\)
5x.5=625
=>5x.5=54
=>5x=54:5
=>5x=54-1
=>5x=53
=>x=3